Nonfullerene Tandem Organic Solar Cells with High Open‐Circuit Voltage of 1.97 V. Issue 44 (16th September 2016) - Liu, Wenqing; Li, Shuixing; Huang, Jiang; Yang, Shida; Chen, Jiehuan; Zuo, Lijian; Shi, Minmin; Zhan, Xiaowei; Li, Chang‐Zhi; Chen, Hongzheng
Abstract : Small‐molecule nonfullerene‐based tandem organic solar cells (OSCs) are fabricated for the first time by utilizing P3HT:SF(DPPB)4 and PTB7‐Th:IEIC bulk heterojunctions as the front and back subcells, respectively. A power conversion efficiency of 8.48% is achieved with an ultrahigh open‐circuit voltage of 1.97 V, which is the highest voltage value reported to date among efficient tandem OSCs.